Development and performance evaluation of low-cost IoT based smart irrigation system for home kitchen garden - THAKRE, ALOK; SINHA, JITENDRA (Journal of Soil and Water Conservation, 2024)
Irrigation scheduling which uses real-time sensors has the potential to boost water use efficiency. A traditional kitchen garden is adversely affected by improper resource management. To overcome a person’s efforts, an IoT based smart irrigation system was developed and tested for system performance. The developed smart irrigation system, consisting of sensors and microcontrollers, records the environmental parameters viz, soil moisture content, temperature, and relative humidity. Irrigation scheduling was programmed for the smart irrigation system using real-time parameters data in the application. In today’s era, everyone can’t eat fresh and good quality vegetables because of the high prices of vegetables. Thus, there will be the need to adopt the home kitchen garden. The smart irrigation system can be operated from anywhere in the world from a smartphone/web. The smart irrigation system helps in the irrigation and fertigation of liquid fertilizers effectively, because of drip line was used along with this system. The key point of this smart irrigation system is its low cost. The components of the system are available in the market so that they can be easily accessible. The cost of the system is only Rs 2650. As it has a low cost, everyone can afford it. The developed system was efficient for urban kitchen garden.